2020
DOI: 10.1155/2020/6930836
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Common Methods for Precision Volume Measurement of Hematoma

Abstract: Purpose. Our aim is to conduct analysis and comparison of some methods commonly used to measure the volume of hematoma, for example, slice method, voxelization method, and 3D-Slicer software method (projection method). Method. In order to validate the accuracy of the slice method, voxelization method, and 3D-Slicer method, these three methods were first applied to measure two known volumetric models, respectively. Then, a total of 198 patients diagnosed with spontaneous intracerebral hemorrhage (ICH) were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
(14 reference statements)
0
17
0
1
Order By: Relevance
“…The other possibility may be associated with pre-existing early infarct prior to EVT, which was supported by the correlation between the scores of CE-ASPECTS and initial ASPECTS of infarct lesions in this study (ρ = 0.31; P < 0.05, Spearman correlation test). Of note, the head of the caudate nucleus manifested similar outcomes to the cortex structures, which could be explained by its shared supply from the anterior cerebral artery, the latter territory of which is often eloquent and not included in ASPECTS grading 13 , 16 , 29 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The other possibility may be associated with pre-existing early infarct prior to EVT, which was supported by the correlation between the scores of CE-ASPECTS and initial ASPECTS of infarct lesions in this study (ρ = 0.31; P < 0.05, Spearman correlation test). Of note, the head of the caudate nucleus manifested similar outcomes to the cortex structures, which could be explained by its shared supply from the anterior cerebral artery, the latter territory of which is often eloquent and not included in ASPECTS grading 13 , 16 , 29 .…”
Section: Discussionmentioning
confidence: 97%
“…Given the possible intersection of threshold ranges between normal brain tissue and CE, the individual threshold range (the maximum and minimum HU values) was set according to the HU value of CE in each patient based on Image J software to assure the reliability and reproducibility of the measurement method. Then, the three-dimensional reconstruction of the CE was realized, and the volume of the CE was calculated automatically 16 .…”
Section: Methodsmentioning
confidence: 99%
“…We cleared the septal cavity and cut off bridging veins with high tension under rigid neuroendoscopy, which promoted hematoma expulsion and prevented rebleeding. 3D modeling was adopted to calculate hematoma volume in 3D Slicer software (Figure 2A), which had been proved to be more accurate than the traditional Tada formula method in hematoma volume calculation (20,21). In our study, rigid neuroendoscopy assisted hematoma resection indicated a higher hematoma clearance compared with traditional BHC.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a follow-up CT was checked once more within 3–4 days after ICH occurrence, considering the time of the MRI. Hematoma volume and rPHE were measured using an open-source 3D-slice software to which the original DICOM format files produced by computed tomography (CT) (3D-Slicer, Harvard University, Cambridge, MA, USA) were uploaded and examined by two neurointerventionists who each had more than 10 years of experience [ 17 ]. rPHE was defined as edema volume divided by hematoma volume.…”
Section: Methodsmentioning
confidence: 99%